2006
DOI: 10.1227/01.neu.0000232988.46219.e4
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Nerve to Suprascapular Nerve Transfer to Restore Shoulder Exorotation in Otherwise Spontaneously Recovered Obstetric Brachial Plexus Lesions

Abstract: An accessory to suprascapular nerve transfer is effective to restore active exorotation when performed as the primary or a separate secondary procedure in children older than 10 months of age. Contradictory spontaneous recovery of other superior trunk functions and integrity of suprascapular nerves, as well as absence of spinatus muscle wasting direct to central nervous changes are possible main causes for the lack of exorotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Reportan buenos resultados con recuperación de la RE del hombro neurotizando el nS en niños solo sin recuperación de la RE. 29 Terzis y Kokalis 15 obtuvieron mejores resultados en pacientes operados antes de los 6 meses de vida, y consideran que una neurotización intraplexual del tronco posterior, en particular del nervio axilar, es fundamental para mejorar los resultados. Trazando un paralelismo con la patología del adulto, Bertelli y Ghizoni comunican también mejores resultados cuando reconstruyen el tronco primario superior y el tronco posterior, probablemente por reinervación de músculos accesorios y antagonistas.…”
Section: Discussionunclassified
“…Reportan buenos resultados con recuperación de la RE del hombro neurotizando el nS en niños solo sin recuperación de la RE. 29 Terzis y Kokalis 15 obtuvieron mejores resultados en pacientes operados antes de los 6 meses de vida, y consideran que una neurotización intraplexual del tronco posterior, en particular del nervio axilar, es fundamental para mejorar los resultados. Trazando un paralelismo con la patología del adulto, Bertelli y Ghizoni comunican también mejores resultados cuando reconstruyen el tronco primario superior y el tronco posterior, probablemente por reinervación de músculos accesorios y antagonistas.…”
Section: Discussionunclassified
“…Following the description of Kawabata and colleagues [9] of the use of the spinal accessory nerve as an ipsilateral nerve transfer to the suprascapular nerve in infants with upper brachial plexus birth injuries, its use has continued to expand. Total the scores for active abduction/forward flexion and active external rotation; from [7] a Maximum shoulder score=10; decrease score by 1 point for a contracture >20°T Several groups [1,6,8,11,14,19,20] have published variable experiences with the use of the distal SAN-to-SSN transfer as part of a primary or secondary plexus reconstruction in infants who fail to demonstrate spontaneous recovery of active shoulder external rotation following a period of observation. In a retrospective review of 86 infants, Pondaag et al [14] found similar clinical results and functional scores in infants undergoing C5-to-SSN bypass grafting (n=65) and those who received direct SANto-SSN (n=21) transfers performed at a mean of 5 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve transfers can be directed toward the suprascapular nerve or the axillary nerve [17,18,22,[24][25][26][27][28][29][30][31][32][33]. In the flail shoulder, the author prefers to perform both nerve transfers to maximize shoulder motion.…”
Section: Nerve Transfers For Shoulder Motionmentioning
confidence: 99%
“…Most of the nerve transfer results in children have addressed shoulder motion [32,33,43]. Kawabata and colleagues [32] reported on 13 spinal accessory nerve transfers to various targets.…”
Section: Outcomes Of Nerve Transfersmentioning
confidence: 99%
See 1 more Smart Citation